Thymoma in dog: case report - Oliveira, Taine (Pubvet, 2021)
Thymoma is a tumor that arises from cells of the thymus, an organ present in all mammals, responsible for the maturation of T lymphocytes and that regresses in size throughout life, until in adulthood it is gradually replaced by adipose tissue. These tumors are more common in elderly animals and the clinical signs associated with this type of neoplasia are often non-specific until they reach large proportions. A preliminary diagnosis of thymoma is often made based on the location of the tumor and aspiration cytology. Compared to other types of tumor that can occur in this region, thymomas usually have a good prognosis with treatment. This article reports the case of a 10-year-old Labrador Retriever dog, diagnosed with thymoma of epithelial origin, who was treated as a thymectomy through intercostal thoracotomy with rib resection. Thymoma was identified through imaging exams such as chest radiography and computed tomography, by aspiration cytology and a diagnosis was confirmed through histopathological examination. The patient had a favorable evolution in the postoperative period and until now, she is in excellent general condition.
Keywords: Oncology; thymus; thymectomy; intercostal thoracotomy; lateral thoracotomy